2008
DOI: 10.1001/archsurg.2007.75
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Utility of Postoperative C-reactive Protein for Posthepatectomy Liver Failure

Abstract: The early dampened CRP response after major liver resection may reflect poor hepatic reserve that could have prognostic utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 42 publications
2
29
0
5
Order By: Relevance
“…However, the study population was heterogeneous, including patients with carcinoma of the biliary tract, benign liver tumors, and metastatic liver tumors. The present study, limited to patients with HCC arising from underlying liver disease, [44] 2009 LM, HCC 1271 Age, cirrhosis Rahman [45] 2008 LM, HCC 138 Resection of ≥5 Couinaud segments Mullen [19] 2007 LM, HCC, CCC 1059 b Age Associated major intraabdominal procedures e Cucchetti [34] 2006 HCC 154 a MELD score Schindl [13] 2005 LM, HCC 104 RLV, BMI Balzan [18] 2005 HCC, LM 775 Age, fibrosis stage Kubo [46] 2004 HCC 251…”
Section: Discussionmentioning
confidence: 99%
“…However, the study population was heterogeneous, including patients with carcinoma of the biliary tract, benign liver tumors, and metastatic liver tumors. The present study, limited to patients with HCC arising from underlying liver disease, [44] 2009 LM, HCC 1271 Age, cirrhosis Rahman [45] 2008 LM, HCC 138 Resection of ≥5 Couinaud segments Mullen [19] 2007 LM, HCC, CCC 1059 b Age Associated major intraabdominal procedures e Cucchetti [34] 2006 HCC 154 a MELD score Schindl [13] 2005 LM, HCC 104 RLV, BMI Balzan [18] 2005 HCC, LM 775 Age, fibrosis stage Kubo [46] 2004 HCC 251…”
Section: Discussionmentioning
confidence: 99%
“…Because CRP is produced in the liver, Rahman et al [19] postulated a dampened CRP could be sign of liver failure. They were able to show that patients developing a PHLF had a significant lower CRP level on POD 1 than patients without PHLF [19]. …”
Section: Risk Factors and Risk Assessment For Phlfmentioning
confidence: 99%
“…Using this definition of liver function, they reported that the future remnant liver limit for safe major hepatectomy was >26.5% for patients with a healthy liver and >31% for patients with impaired liver function. Rahman et al [32] defined PHLF on postoperative day 7 as persistent hyperbilirubinemia (serum bilirubin level >4.1 mg/dL), coagulopathy (INR >2.5) despite early attempts on correction with clotting factors, ascites (drainage volume >500 mL/day), encephalopathy with hyperbilirubinemia, and exclusion of other acute confusional states. They also reported serum C-reactive protein level on day 1 and extent of resection as independent predictors of PHLF by multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%